The isolation, characterisation and granular formulation of native entomopathogenic nematodes in South Africa - Didiza, Linda Tabile (My University, 2020)
Entomopathogenic nematodes (EPNs) are obligate pathogens in nature and are used in the biological control of insect pests of agricultural crops. Nematodes are simple, colourless, unsegmented, bilaterally symmetrical, pseudocoelomic, triploblastic, worm-like animals, enclosed within a tough, elastic, and flexible, chitin containing cuticle. Entomopathogenic nematodes belonging to the genera Steinernema and Heterorhabditis are symbiotically associated with insect pathogenic bacteria belonging to the genera Xenorhabdus and Photorhabdus, respectively. The focuses of this research was to isolate, identify, phylogenetically analyse, and formulate entomopathogenic nematodes indigenous to South Africa. The entomopathogenic nematodes were isolated from soil samples originally collected in Brits and Walkerville. Subsequent to their collection the soil samples had been stored for a prolonged period (> 2years) in a dehydrated state. To isolate EPNs the soil samples were rehydrated and baited with Galleria mellonella larvae. The methods used for the identification and phylogenetic analysis of the isolated nematodes involved genomic DNA extraction, PCR amplification of 18S rDNA and Sanger sequencing of the18S rDNAamplicons. The entomopathogenic nematodes that were isolated included Heterorhabditis bacteriophora isolate 56-C and a new previously uncharacterised Steinernema species. Another focus of the research was to isolate and identify the bacterial symbionts of the isolated entomopathogenic nematodes. The methods used for the isolation of the bacterial symbionts involved haemolymph extraction from the infected larvae and homogenisation of sterilized infective juveniles. The methods used for the identification and phylogenetic analysis of the isolated entomopathogenic bacterial species involved total genomic DNA extraction, PCR amplification of 16S rDNA,and Sanger sequencing of the16 rDNA amplicon. The isolated bacteria were identified as Xenorhabdus sp VP and Photorhabdus luminescens subspecies sonorensis Carbonca. The study also showed that the isolated entomopathogenic nematodes had survived in soils that had been kept in a state of complete dehydration for a prolonged period. The survival of infective juveniles in the desiccated soil could have been due to the induction of anhydrobiosis or dehydration tolerance. Thus, the aim of this study also involved an investigation into the possible induction of anhydrobiosis or dehydration toleration in formulated infective juveniles by regulating the rate of moisture loss from various formulation media used. In the study, the Heterorhabditis bacteriophora isolate 56-C was formulated in different hydroscopic or water-absorbing powders which included diatomaceous earth, crystalline cellulose and clay. Results showed that the rate of moisture loss from the formulation media had a significant impact on the viability of formulated infective juveniles. The finding was interpreted as evidence supporting the hypothesis that the induction of anhydrobiosis or dehydration tolerance depends strongly on the rate of dehydration. Both the comparative morphometric characterization and phylogenetic analysis of the previously uncharacterised Steinernema sp confirmed that it was a new species of Steinernema. The results showed that the average length of the infective juveniles was 975μm with a standard deviation of 72μm, therefore, the species fell under the glaseri-group of Steinernema. Phylogenetic analysis showed that the new species did not form a clade with any of the local Steinernema species, therefore, confirming that the species isolated from Brits was, in fact, a new species
A dissertation submitted in fulfilment of the requirements for the degree Master of Science in Molecular and Cell Biology in the Faculty of Science, University of the Witwatersrand, 2020
Keywords: Nematodes; Insect nematodes